an Analysis of Students’ Error in Constructing the Negative and Interrogative Sentence by Using Simple Present Tense - Diana Adinda Shafira; Rabbayani Mawaddah; Lidya Br Aritonang; Elianti Nainggolan; Natalia Widya Pasca Tarigan (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research aims to find out the errors made by the students in constructing the negative and interrogative sentences by using the simple present tense. Those errors were classified into four types, namely omission, addition, misformation, and misordering based on surface strategy taxonomy from Daulay. The researchers used a descriptive qualitative method to find the result. The subject of this research was the VIII-A class of SMP Negeri 40 Medan that consisted of 30 students. The instrument for gathering the data was the essay test, which included 20 affirmative sentences, which asked to form those sentences into the negative and interrogative sentences. The findings indicated that the students' errors in this study were 318 (50,4%) case of mistakes on misformation; 175 (27,8%) case of errors on addition; 100 (15,9%) case of errors on misordering; and 37 (5,9%) case of errors on omission. It can be concluded that misformation in the most frequent errors, while failure is the rarest error in this research. Keywords: error analysis, constructing negative and interrogative sentence